2018
DOI: 10.1051/matecconf/201815401034
|View full text |Cite
|
Sign up to set email alerts
|

The effect of temperature and time of extraction on the quality of Semi Refined Carrageenan (SRC)

Abstract: Euchema cottonii is a good source of kappa-carrageenan and can be found cultivated in the Indonesia coastal areas in which one of them is in Banten Province. Carrageenans have many applications and are utilized in human food and pet-food industry. Carrageenans are also utilized in non-food industry such as pharmaceuticals, cosmetics, printing and textile formulations. Hence, the present study features on the cooking process cooking time and cooking temperature. The effects of these parameters on carrageenan qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 7 publications
(2 reference statements)
0
14
0
5
Order By: Relevance
“…Temperature can affect the yield and quality of carrageenan, as observed in K . alvarezii (formerly known as Eucheuma cottonii ) [ 6 ]. Our present study, which showed that seaweeds incubated at 32, 36 and 40°C produced significantly lower carrageenan yield compared to seaweeds incubated at 28°C, corroborate with previous studies [ 53 55 ], which reported that incubation of seaweeds beyond conducive temperature lowers their gel strength and gel viscosity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Temperature can affect the yield and quality of carrageenan, as observed in K . alvarezii (formerly known as Eucheuma cottonii ) [ 6 ]. Our present study, which showed that seaweeds incubated at 32, 36 and 40°C produced significantly lower carrageenan yield compared to seaweeds incubated at 28°C, corroborate with previous studies [ 53 55 ], which reported that incubation of seaweeds beyond conducive temperature lowers their gel strength and gel viscosity.…”
Section: Discussionmentioning
confidence: 99%
“…Carrageenan is a family of gel-forming, viscosifying polysaccharides [ 5 ] consisting of sulfated galactans with a backbone of alternating 4-linked α-D- galactopyranosyl and 3-linked β-D-galactopyranosyl monomers. In an effort to improve the economic value, seaweeds are made into Semi Refined Carrageenan (SRC), via a process to meet the quality standards of food (food grade) [ 6 ]. The price of seaweed could reach US$ 3.50 to US$ 5.50 per kg once processed into SRC and the value of seaweed carrageenan increases to US$ 9 per kg after Refined Carrageenan (RC) production [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Persentase rendemen tertinggi masing-masing sampel didapatkan pada konsentrasi 6% dengan waktu ekstraksi 60. Menurut Heriyanto et al (2018) penggunaan suhu ekstraksi yang tinggi dengan waktu yang lama dapat meningkatkan rendemen karagenan. Semakin lama waktu ekstraksi menyebabkan pengikatan gugus sulfat pada rantai keenam semakin lama yang mengakibatkan pembentukan 3,6-anhidrogalaktosa semakin banyak, meskipun pada hasil penelitian ini lama waktu ekstraksi dan konsentrasi KOH tidak memberikan pengaruh signifikan pada rendemen SRC yang dihasilkan.…”
Section: Rendemenunclassified
“…Semakin lama waktu ekstraksi semakin rendah viskositas yang dihasilkan. Heriyanto et al (2018) pada penelitiannya menemukan bahwa karagenan semi-murni yang diekstraksi dengan waktu ekstraksi yang lebih lama mengalami penurunan nilai viskositas yaitu 337,5 cP pada lama ekstraksi 1 jam dan 70 cP pada lama ekstraksi 3 jam. Kondisi tersebut disebabkan oleh penurunan jumlah gugus sulfat pada karagenan yang dihasilkan serta tingginya pembentukan 3,6-anhidrogalaktosa dapat menurunkan viskositas larutan karagenan.…”
Section: Kappaphycus Alvarezii Kappaphycus Striatumunclassified
See 1 more Smart Citation